2017
DOI: 10.17267/2238-2704rpf.v7i4.1602
|View full text |Cite
|
Sign up to set email alerts
|

A Experiência Parental Após O Diagnóstico Da Microcefalia Por Zika Vírus: Um Estudo De Caso

Abstract: | Objective:To report the parental experience after receiving the diagnosis of microcephaly by zika virus. Methods: A qualitative methodology was applied as a single case study type. The key informants were parents of a child with microcephaly by zika virus. The data collection instrument was the semi-structured interview, later analyzed and categorized through content analysis, based on Minayo's theory. The research was approved by the Ethics and Research Committee of the UNEB, under the protocol number 09861… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
1
3
0
15
Order By: Relevance
“…After the diagnosis, mothers should be guided on the repercussions imposed by the diagnosis, since most of them do not have the actual knowledge about the child's condition, the causes and the possible consequences, as observed in this study. Research on children with chronic diseases found that the mothers showed partial knowledge about the child's condition, not understanding what caused the occurrence of the clinical condition, when it occurred and the motor and cognitive repercussions, which corroborates the present study (7,13) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…After the diagnosis, mothers should be guided on the repercussions imposed by the diagnosis, since most of them do not have the actual knowledge about the child's condition, the causes and the possible consequences, as observed in this study. Research on children with chronic diseases found that the mothers showed partial knowledge about the child's condition, not understanding what caused the occurrence of the clinical condition, when it occurred and the motor and cognitive repercussions, which corroborates the present study (7,13) .…”
Section: Discussionsupporting
confidence: 89%
“…Another research on the experience of parents after the diagnosis of microcephaly by ZIKV observed that fathers and mothers can go through a moment of denial, looking at the children as they had no disease. After denial, an initial phase of destabilization occurs, followed by an adaptation, in which the parents end up accepting the child's diagnosis and perceiving the child's needs, thus establishing a relationship of affection and patience (7,(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nota-se a intermediação das repercussões pelas tecnologias diagnósticas e sobre este aspecto, as reflexões da Sociologia do Diagnóstico podem fornecer elementos importantes a essa discussão ao trazer o diagnóstico como categoria, processo e consequência (21) . O diagnóstico intrauterino de microcefalia é mediado, portanto, duplamente pelo exame do corpo da mulher e do feto (20) , que se repercutem (consequências) de modo diferenciado em todos envolvidos (21,22) Considerar a situação das gestantes e familiares em relação aos procedimentos diagnósticos permite abordar o diagnóstico como um ato, um processo interpretativo, que se desdobra em emoções, saberes e nas interações, em particular, com os serviços e profissionais de saúde, produzindo efeitos que repercutem muito além do hospital e/ou consultório do médico (21) para espraiar-se nas interações e arranjos familiares ao incidir sobre seus planos e projetos futuros.…”
Section: Repercussões E Apoios Cotidianos Na Gestação Com Suspeita Ouunclassified
“…As mais diversas necessidades sociais exigem suporte e melhor administração dos recursos financeiros, assim como, o estabelecimento de prioridades para a destinação desses recursos, que pode, a depender das condições financeiras de cada família, modificar projetos individuais/coletivos futuros (18,22,23) .…”
Section: "Eu Fiquei Desesperado Chorei Pensei Muito O Porquê Disso unclassified